ANALISIS KUALITAS PADA PRODUKSI LABELSTOCK KERTAS HVS DI PT â€œXâ€ - Purtomo, Tjahjo (Heuristic, 2016)
PT. "X" one of the manufacturing industry engaged in the manufacture of paper labels, release liner and packaging tape, and while also receiving another product label orders. The process of coating on this company using wet glue placed on release paper is then dried using a dryer, so that the glue dries quickly, and then combined with certain items. In order to guarantee the quality of products, the company implemented a control chart X and R are used to measure the uniformity of the thickness of the glue on all sides, and the cause and effect diagram is used to infer the cause of the difference in the thickness of the glue on labelstock production. With the above method, the obtained results that the Lower Control Limit 20 Limit Control Over 22, and the target of 21. Cp value of 0.19 (Cp < 1) means that the process is not capable. While the resulting Cpk value of 0.05 (Cpk< 1), we conclude that the thickness of the glue is not capable or not of accuracy and precision. The cause of differences in the thickness of the glue is supposedly 5 factors, namely human factors, raw materials, machines, methods and environment. The cause of differences in the thickness of the glue is supposedly 5 factors, namely human factors, raw materials, machines, methods and environment. Kata kunci : Pengendalian Kualitas, Labelstock